Efektivitas Pengendalian Internal Pada Praktik Akuntansi Sebagai Upaya Mitigasi Dan Deteksi Terhadap Fraudulent Pada Perusahaan - Fatwa Nabila F.E; M. Rakha Rafiansyah Rizq (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to examine the influence of Internal Control Effectiveness and Accounting Practices on the level of Fraudulent Activities within companies. The data analysis reveals that both independent variables have a significant impact on the dependent variable. The Internal Control Effectiveness shows a positive and significant correlation with Fraudulent Activities, while Accounting Practices exhibit a negative and significant correlation. Partial T-tests confirm that each variable individually affects Fraudulent Activities. Additionally, the simultaneous F-test indicates that Internal Control Effectiveness and Accounting Practices together have a significant impact on Fraudulent Activities. Multicollinearity and heteroscedasticity tests show no serious issues related to classical assumptions, and the autocorrelation test indicates no autocorrelation in the model residuals. These findings suggest that improving internal controls and accounting practices can significantly reduce the risk of fraud within companies.